Primary cutaneous indolent B-cell lymphomas – a retrospective multicenter analysis and a review of literature. (3rd October 2021) - Olszewska-Szopa, Magdalena; Sobas, Marta; Laribi, Kamel; Bao Perez, Laura; Drozd-Sokołowska, Joanna; Subocz, Edyta; Joks, Monika; Zduniak, Krzysztof; Gajewska, Małgorzata; de Nalecz, Anna Kulikowska; Romejko-Jarosińska, Joanna; Kumiega, Beata; et al.
Abstract: Introduction: Primary cutaneous indolent B-cell lymphomas (PCBCLs) are not well characterized due to their rarity and indolent character. Methods: We retrospectively reviewed the data from 52 patients with primary cutaneous follicular lymphoma (PCFL) ( n = 26), marginal zone lymphoma (PCMZL) ( n = 25) or undefined PCBCL ( n = 1) treated in 10 hematology centers in 1999–2019. Results: Patients characteristics and diagnostic approach: In almost half of the patients, pruritus or pain were present at diagnosis. The lesions were predominantly located on the head and trunk. The disease was present in a form of solitary infiltration or disseminated lesions with a similar frequency. Treatment details and outcomes: Surgery, radiotherapy, rituximab alone or combined with chemotherapy were applied as first-line treatment in 33%, 25%, 21% and 21% of patients, with complete response (CR) achieved by 94%, 83%, 50% and 70% of patients, respectively ( p = 0.28). The median duration of response (DoR) was 65 months (95%CI 35–155). Survival: After the median follow-up time of 46 months (range: 3–225), the estimated 5-year overall survival (OS) and progression-free survival (PFS) were 93% and 54%, respectively. Discussion: Clinical presentation was largely consistent with the literature data, however, we observed some differences, including higher predilection to affect upper extremities (25%) and more frequent multifocal appearance in PCFCL (64%) and unifocal in PCMZL (70%). A high proportion of patients with indolent PCBCL achieved CR after the first-line therapy (77%), regardless of treatment mode. We did not find any impact of clinical features on treatment outcomes. Conclusions: All treatment modalities resulted in a high overall response rate. Surgery and/or radiotherapy are the optimal therapeutic options for patients with localized disease. The decision to treat systemically should rather be limited to the generalized form of the disease. High response rate, long duration of remission and excellent long-term survival confirm the truly indolent character of PCFCL and PCMZL.